Digenic inheritance of mutations in HAMP and HFE results in different types of haemochromatosis. - Merryweather-Clarke, A; Cadet, E; Bomford, A; Capron, D; Viprakasit, V; Miller, A; McHugh, P; Chapman, R; Pointon, J; Wimhurst, V; Livesey, K; Tanphaichitr, V; et al. (2003)
Haemochromatosis (HH) is a clinically and genetically heterogeneous disease caused by inappropriate iron absorption. Most HH patients are homozygous for the C282Y mutation in the HFE gene. However, penetrance of the C282Y mutation is incomplete, and other genetic factors may well affect the HH phenotype. Ferroportin and TFR2 mutations also cause HH, and two HAMP mutations have recently been reported that causes juvenile haemochromatosis (JH) in the homozygous state. Here, we report evidence for digenic inheritance of HH. We have detected two new HAMP mutations in two different families, in which there is concordance between severity of iron overload and heterozygosity for HAMP mutations when present with the HFE C282Y mutation. In family A, the proband has a JH phenotype and is heterozygous for C282Y and a novel HAMP mutation Met50del IVS2+1(-G). This is a four nucleotide ATGG deletion which causes a frameshift. The proband's unaffected mother is also heterozygous for Met50del IVS2+1(-G), but lacks the C282Y mutation and is heterozygous for the HFE H63D mutation. Met50del IVS2+1(-G) was absent from 642 control chromosomes. In family B, a second novel, less severe HAMP mutation, G71D, was identified. This was detected in the general population at an allele frequency of 0.3%. We propose that the phenotype of C282Y heterozygotes and homozygotes may be modified by heterozygosity for mutations which disrupt the function of hepcidin in iron homeostasis, with the severity of iron overload corresponding to the severity of the HAMP mutation.